(untitled) (JURNAL KESEHATAN MERCUSUAR, 2023)
Stunting is a national problem related to chronic malnutrition which occurs due to multifactors including nutritional intake, nutritional parenting, genetics, infectious diseases and hygiene. Currently, breakthrough interventions and real action are needed to overcome editing problems. This research aims to determine the effectiveness of the educational video for making the MPASI 4 Star menu on the knowledge, attitudes and skills of parents in preventing stunting in toddlers. The research design used is quantitative, quasi-experimental research using a one group pretest posttest design approach. This research was conducted on parents of toddlers in DKI Jakarta with a sample size of 44 respondents. The results showed that there was a significant difference in knowledge before and after the intervention (p value 0.000), there was a significant difference in attitudes before and after the intervention (p value 0.000), there was a significant difference in skills before and after the intervention (p value 0.000 ). It is hoped that this research can be an alternative action in the form of education via video for parents to overcome stunting in toddlers and to develop care, further research can be carried out regarding interventions to deal with stunting.